Cigarette smoking is an independent risk factor for post-stroke delirium - Lim, Tae Sung (BMC Neurol, 2017)
BACKGROUND: Post-stroke delirium is a common problem in the care of stroke patients, and is associated with longer hospitalization, high short-term mortality, and an increased need for long-term care. Although post-stroke delirium occurs in approximately 10 ~ 30% of patients, little is known about the risk factors for post-stroke delirium in patients who experience acute stroke. METHODS: A total of 576 consecutive patients who experienced ischemic stroke (mean age, 65.2 years; range, 23–93 years) were screened for delirium over a 2-year period in an acute stroke care unit of a tertiary referral hospital. We screened for delirium using the Confusion Assessment Method. Once delirium was suspected, we evaluated the symptoms using the Korean Version of the Delirium Rating Scale-Revised-98. Neurological deficits were assessed using the National Institutes of Health Stroke Scale at admission and discharge, and functional ability was assessed using the Barthel Index and modified Rankin Scale at discharge and 3 months after discharge. RESULTS: Thirty-eight (6.7%) patients with stroke developed delirium during admission to the acute stroke care unit. Patients with delirium were significantly older (70.6 vs. 64.9 years of age, P = .001) and smoked cigarettes more frequently (40% vs. 24%, P = .033) than patients without delirium. In terms of clinical features, the delirium group experienced a significantly higher rate of major hemispheric stroke (55% vs. 26%, P < .001), exhibited poorer functional performance at discharge and 3 months after discharge, and stayed in hospital significantly longer. Independent risk factors for delirium were older age, history of cigarette smoking, and major hemispheric stroke. CONCLUSION: Abrupt cessation of cigarette smoking may be a risk factor for post-stroke delirium in ischemic stroke patients. The development of delirium after stroke is associated with worse outcome and longer hospitalization.